2010
DOI: 10.1002/cpe.1608
|View full text |Cite
|
Sign up to set email alerts
|

Performance modelling and analysis of Deficit Round Robin scheduling scheme with self‐similar traffic

Abstract: SUMMARYThe provisioning of fairness to various network applications is an important Quality-of-Service demand and has thus become a challenging research issue in contemporary communication networks. Deficit Round Robin (DRR) is a promising fair scheduling mechanism owing to its low complexity and excellent ability of achieving a good degree of fairness in terms of throughput. On the other hand, self-similar traffic was found to be pervasively present in communication networks and has great impact on the perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Liu et al (2010) studied that a fair scheduling mechanism had an excellent ability and having low complexity [17]. In a communication network, it was observed that self-similar traffic was persistently presented.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al (2010) studied that a fair scheduling mechanism had an excellent ability and having low complexity [17]. In a communication network, it was observed that self-similar traffic was persistently presented.…”
Section: Related Workmentioning
confidence: 99%
“…This is truly the most important improvement of DRR compared to the original round robin scheme. It is clear that the service assigned to each flow depends only on its fixed quantum and any greedy traffic flows cannot take away the remaining service of the other flow [17]. Flow diagram of DRR is shown in Fig.…”
Section: A Deficit Round Robinmentioning
confidence: 99%
“…To demonstrate its applications, the analytical model is used to investigate the effects of packet size on the performance of the queuing system. The developed model is further applied to study the configuration of weights of individual traffic flows [4].…”
Section: Papers Presented In This Special Sectionmentioning
confidence: 99%